2014
DOI: 10.1007/978-94-017-8029-2_21
|View full text |Cite
|
Sign up to set email alerts
|

The Andaman Archipelago

Abstract: The Andaman Archipelago of the north-eastern Indian Ocean is made up of more than 570 islands and islets, formed along the convergent margin of the Indian and Burmese Plates. These islands are either located on the accretionary prism or on the volcanic arc of the subduction zone. Began forming more than 20 Ma ago the archipelago is home to some of the spectacular and scientifically significant tectonic, volcanic, coastal and erosional landforms. This chapter describes some of these landforms and discusses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The subaerial portion of the ridge is made up of >500 islands, two of which are volcanic (Narcondam and Barren; Figure a). As mentioned above, most of these islands are surrounded by coral reefs since the LGM [ Awasthi et al ., ; Ray , ], which would not have formed if the sediment discharge was significant. In addition, there exist several underwater ridges, located to the east of these islands, which may obstruct sediment discharge.…”
Section: Probable Sediment Sources and Their Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subaerial portion of the ridge is made up of >500 islands, two of which are volcanic (Narcondam and Barren; Figure a). As mentioned above, most of these islands are surrounded by coral reefs since the LGM [ Awasthi et al ., ; Ray , ], which would not have formed if the sediment discharge was significant. In addition, there exist several underwater ridges, located to the east of these islands, which may obstruct sediment discharge.…”
Section: Probable Sediment Sources and Their Compositionmentioning
confidence: 99%
“…No study as yet has confirmed the existence of sediment dispersal from the BoB into the Andaman Sea, whereas the converse has been established [e.g., Ramaswamy et al ., ; Rao et al ., ]. Andaman Islands, located within the north‐eastern Indian Ocean (Figure ) also experience heavy rainfall during the SW and NE monsoons and the rocks exposed on it are highly weatherable akin to the IBA ranges; however, limited areal extent (< 5000 km 2 ), lack of ample drainage and presence of coral reefs/underwater ridges [e.g., Ray , ] make these islands a minor source of sediments.…”
Section: Introductionmentioning
confidence: 99%